Do genome‐scale models need exact solvers or clearer standards?. Issue 10 (14th October 2015) - Ebrahim, Ali; Almaas, Eivind; Bauer, Eugen; Bordbar, Aarash; Burgard, Anthony P; Chang, Roger L; Dräger, Andreas; Famili, Iman; Feist, Adam M; Fleming, Ronan MT; Fong, Stephen S; Hatzimanikatis, Vassily; et al.
Abstract : Recent results obtained by Chindelevitch et al (2014) are challenged by Ebrahim et al, illustrating several issues in the reproducibility of computational biology methods.